Introduction to genomics in primary care. Issue 2 (February 2021) - Whiter, Alexandra; Sheridan, Eamonn; Hayward, Judith; Rafi, Imran
Advances in genomic technology and the launch of the NHS Genomic Medicine Service (GMS) in 2018 have firmly embedded genomic testing within routine clinical care. As the gateway to the NHS, primary care practitioners will be managing increasing numbers of patients who are eligible for genomic testing, or who present with their own, or a family member's genomic test result. This article provides an overview of recent developments in the field of genomics, explains key concepts and terminology, and details the current organisation of the genomics services under the GMS. It also discusses some common presentations within primary care to highlight the relevance of genomics to frontline GPs.